Avaliação institucional: entre políticas e práticas - Barbosa, Vera Maria (2011)
The purpose of this study is to examine the process of institutional evaluation in private higher education, especially the self-evaluation commission, an academic representative body created by higher education institutions, in accordance with the law 10.861/2004 which established the National System for the Evaluation of higher Education (SINAES). SINAES provides higher education institutions with indicators in order to improve the quality of higher education. In order to understand this process, the following authors have contributed to this study: José Dias Sobrinho, Valdemar Sguissardi, Guilherme Marback Neto, Maria Amélia Sabbag Zainko, Maria Helena de Oliveira Guimarães, Maria de Lourdes Fávero, Boaventura Souza Santos. This research work begins with scenario’s description of national assessment, deals with the main aspects and analyses the final reports of three different academic institutions: Faculty, University Centre, and a private University in the city of Curitiba. This study which covers the legal aspects and the diagnostic description contained in the Final Reports was developed through an exploratory, documental and bibliographic qualitative research and through an analysis of reports and application of a semi-structured questionnaire. Finally, it has been observed that the selfevaluation-commission may promote institutional improvement concerning academic and administrative issues and introduce changes in the institutions.